Improving Employee Productivity: Compensation, Work Discipline, and Motivation - Hayati, Nur; Farisi, Salman (Cattleya Darmaya Fortuna, 2025)
The purpose of this study is to determine the effect of compensation on employee productivity at the Medan City MSME Cooperative Office, the effect of work discipline on employee productivity at the Medan City MSME Cooperative Office and the effect of motivation on employee productivity at the Medan City MSME Cooperative Office as well as to determine the influence of compensation, work discipline and motivation on employee productivity at the Medan City MSME Cooperative Office. The method in this study using a quantitative approach. The population in this study were all employees of the Medan City UMKM Cooperative Service, totaling 40 people. The sample in this study was sampled using the saturated sample method where all members of the population were sampled as many as 40 people. Data collection techniques in this study used questionnaires or questionnaires distributed to employees of the Medan City UMKM Cooperative Service. The data technique in this study used the calssical assumption test, multiple linear regression, hypothesis testing (t test and F test), and the coefficient of determination. Data processing in this study uses the application Statistical Product and Service Solutions (SPSS) 22.0 for windows. The results of this study show that in terms of compensation, work discipline and motivation, each have a significant effect on the productivity of employees of the Medan City MSME Cooperative Office and simultaneously compensation, work discipline and motivation have an effect on employee productivity at the Medan City MSME Cooperative Office. Further research can add other variables such as leadership, organizational culture, or work-life balance to gain a broader understanding of the factors that affect employee productivity. .